Bandar Udara Sukadana - Fitriani, Meta Indah (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2013)
Currently, air transportation become the modes of transport that receive high demand by residents of Indonesia for long distance movement of man and goods. In order to make the air transportation operations run properly, it needs a well designed airport as the air transportation medium. Airports run a very important role as connector between passangers and the air transportation itself. Therefore, new airports in various regions in Indonesia prepared by the government in order to have larger area for the air transport. West Kalimantan Government targets the construction of three new airports to anticipate the growth of goods and services, one of which will be built in Sukadana (North Kayong District). North Kayong as a new autonomous region needs an airport to open up air transportation to reach the areas that are still isolated. Considering the importance of airports as one of the gates of North Kayong District that may affect the progress of the region, the design of the Sukadana Airport should be based on national standards and fulfill the convenience factors for users to achieve the safe, comfortable and efficient air transportation system in the region. The outer space and inner space organisation of Sukadana Airport designed to be simple with circulation layouts which is clear and easy to understand by passengers and other users. Therefore, the activities in the airport will work well because the cross circulation between passengers can be minimized. In addition, as a building that represents the image of the region, Sukadana Airport uses Malay architectural character that applied in the form of the roof, ornamentations, buildings color, etc.Keywords: Airport, Sukadana, Circulation